Distribution of Handgrip Force in the Forearm Muscles through Static Optimization - Restrepo Correa, Jorge Hernán; Hernandez Arellano, Juan Luis (2020)
The purpose of this work was to distribute the hand grip force between the muscles of the hand by means of a non-linear model solved with static optimization. The force was measured in three pairs of flexion angles corresponding to the shoulder and elbow. (90°-90°, 135°-45°, and 160°- 30). A total of 22 participants completed the study, 6 men and 6 women between 18 and 25 years old. A MicroFET® handgrip dynamometer (0-200 pounds) and an adjustable angle arm support were used during the data collection. The moment arms of the forearm were predicted using a model proposed in the literature. The distribution of force was modeled as a non-linear problem of static optimization and solved with the fmincon optimizer of the Matlab® optimization toolbox. The results obtained in the calculation of the moment arm show that they decrease as the angle of flexion of the elbow decreases. The static optimization model used for the three scenarios related to the flexion angle of the elbow always assigned muscle force to the extensor muscles.